(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The high and growing burden of physical inactivity stresses the need for effective implementation of evidence-based physical activity programmes (PAPs) across the life course. However, interventions with proven efficacy often underperform in real world settings due to insufficient adaptations and inadequate consideration of local implementation barriers. This leads to programme failure and exacerbates public health inequalities. In collaboration with Sport Ireland’s Active Cities project, the Irish Physical Activity Collaboration, which brings researchers, policymakers, and practitioners together to enable more people in Ireland to be more active (I-PARC, see https://i-parc.ie/), aims to identify and map evidence-based community PAPs across Ireland. Methods: Within I-PARC 2.0 work package one involved the development of a national repository of community-based PAPs targeting various life stages. Search strategy included structured desk-based enquiries, exploration of national and international repositories and databases, and consultation with experts and stakeholders. PAPs of 12 weeks or less were included. Information on target-population, delivery format, core and optional PAP components, cost and evidence of efficacy were extracted and synthesised into an excel spreadsheet, circulated to experts and stakeholders for validation to assist with data completeness. Results: A total of 123 community-based PAPs were identified, of which 21 (17%) had an evidence-base indicating their effectiveness. These comprised five older adults, seven children/adolescents, two adults (>18 years), six with no age category and one other. Programmes varied in modality (walking, resistance exercises, home-based programmes), in delivery formats (group, individual, hybrid), in programme design, in clarity on core components, in accessibility to evidence and potential for scalability, highlighting both established and underutilised approaches. Multiple gaps were also established. Conclusion: The resulting repository offers a structured, practice-informed resource to guide stakeholder decision-making and enable context-specific selection of the PAPs that are best aligned to local need, feasible, and consider equity. The next steps for I-PARC 2.0 are to develop a systematic approach to PAP adaptation and to tailored implementation strategies to enhance their real-world reach and effectiveness.